Low Serum Levels of Myeloid Progenitor Inhibitory Factor-1 Predict Good Response to Methotrexate in Rheumatoid Arthritis. (24th December 2013) - Dhir, Varun; Sandhu, Amit; Gupta, Nidhi; Dhawan, Veena; Sharma, Shefali; Sharma, Aman
Abstract : Background . Although the benchmark in the treatment of rheumatoid arthritis remains methotrexate, only 70% of patients respond. Thus, there is a need for predictive biomarkers. This study planned to evaluate serum levels of myeloid progenitor inhibitory factor-1 (MPIF-1) and monocyte chemoattractant protein 2 (MCP-2)—as biomarkers. Methods . Patients with rheumatoid arthritis (RA) having high disease activity (DAS28-3v ≥ 5.1) were treated with oral methotrexate (MTX) for 12 weeks. Disease activity was measured by DAS28-3v (Modified Disease Activity Score 3 variables). Serum samples were stored at baseline and 12 weeks. Results . This study included 46 patients (F : M = 35 : 11) having mean (±SD) age of 42.6 ± 11.3 yrs, disease duration of 4.7 ± 4.5 yrs, and DAS28-3v of 6.1 ± 0.8. Serum MPIF1 was elevated in patients compared to controls (1636.7 ± 1009.7, 441.2 ± 173.8 pg/mL, P < 0.001 ), but there was no difference in MCP2 levels (31.4 ± 11.9, 33.8 ± 24.0 pg/mL). Baseline MPIF-1 level was lower in good responders (ΔDAS28-3v ≥ 1.2, N = 9 ) compared to poor responders (ΔDAS28-3v < 0.6, N = 27 ) (1171.0 ± 670.8, 1816.7 ± 1154.1 pg/mL, P = 0.05 ). On ROC analysis, baseline MPIF1 performed reasonably to predict good response; that is, ΔDAS28-3v ≥ 1.2 (AUC 0.68, 95% CI 0.50–0.87). Conclusions . Lower baseline MPIF1 level predicted a good response to methotrexate at 12 weeks.